THE EFFECT OF USING MONTESSORI METHOD AND DEMONSTRATION METHOD ON STUDENTS’ ACHIEVEMENT IN PRONUNCIATION AT PRIMARY 1 STUDENTS OF NAKAMURA SCHOOL MEDAN - Susanti Susanti (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Pronunciation is one of important aspects in English and one of the necessary components of oral communication. The purpose of this research is to find out Montessori Method and Demonstration Method effect on students’ Achievement in Pronunciation at Nakamura School. The method of this research based on experimental quantitative research doing with using a number, statistics process and structure. The population of this research will use to the primary 1 students of Nakamura School Medan. The writer used simple Random Sampling that is subset of individuals 9 a sample (chosen from a larger set 9 a population), each individual is chosen randomly and entirely. After collecting and analyzing the data, it was found that the lowest score of pre-test in experimental group was 20 and the highest score was 40 and the mean of pre-test was 30.00 and after administrated the method of Montessori method, the researcher found the lowest score of students’ pronunciation was 40 and the highest score was 80 and the mean of post-test was 61.43. It means that there was 20 (40-20) difference of the lowest score in pre-test and post-test. The mean score of the pre-test was 30.00, and the post-test is 61.43 (61.43 – 30.00 = 31.43). It can be concluded that the students’ scores in pre-test of experimental group was smaller than post-test, which was using Montessori method. The lowest score of pre-test in experimental group by Demonstration method was 10 and the highest score was 30, and the mean of pre-test was 22.86. After post-test was administered, the lowest score in experimental group was 50 and the and the highest was 80 and the mean of post-test was 61.43. The lowest score significantly improved. It means that the difference of the score was 50 (100-50). It also happened to the highest score, 80 improved to 100 (100-80 = 20). It means that the difference of the score was 30. The mean of pre-test was 22.86 and post-test was 61.43 (61.43- 22.86= 38.27). It can be concluded that the students’ score in the experimental group which was taught by applying Montessori method was significantly different and the students’ score in pre-test of experimental group was smaller than post-test , which was Demonstration method.